PENANGANAN FAKIR MISKIN DITINJAU DARI KONSEP-KONSEP PEKERJAAN SOSIAL - Sitepu, Anwar (Sosio Informa : Kajian Permasalahan Sosial dan Usaha Kesejahteraan Sosial, 2017)
This paper aims to mendiskripsikan the poor (FM) handling in the perspective of social work. The perspective of the social work in the handling of the poor is described using the concepts of social work major. The concepts referred to are: self-help, human rights, social justice, needs, the source of fulfillment, person – in – the situation, social functioning and planned changed. Refer to the concepts, then the poor handling in the perspective of social work are as follows: the poor is seen as a subject who has dignity and self-respect are the same as other humans. FM understood in relation to its social environment, where he resides. FM is seen as a person who has the potential inherent in himself and in relation to the environment. Therefore, the handling capacity in addition to FM, also with self pen enhancement the capacity of the source systems and the fight for social justice in the community. Activities handling FM needs to be done programmatically and systematically involving various stakeholders, and conducted gradually from: Engagement, Assessment, planning, implementation, evaluation and Termination. Keywords: poor, perspective, social work.